Weighing the factors—the perils of trustee decision-making. Issue 1 (31st October 2021) - Lincoln, Bruce; Hooper, Katie
Abstract: In B v Erinvale PTC Limited & O'rs 2020 (2) JLR 316 ( Erinvale ), the Royal Court of Jersey has handed down a judgment which has important implications for trustee decision-making processes. In the context of a divorce between two of the beneficiaries (the husband also being the settlor), the trustee was requested to add the wife as a beneficiary of the relevant trust in her own right, her beneficial status being contingent at that time on her being the settlor's spouse. The judgment in Erinvale, in which the Court scrutinised whether the wife's request had been correctly decided by the trustee, stands as a stark illustration of the exacting standards which trustees are expected to meet.